Discrimination against homosexuals and lesbians in the state of Hidalgo, Mexico. Approaches to the profiling of agents of discrimination - Mejía Reyes, Carlos (2019)
Discrimination against homosexuals and lesbians in Mexico is perceived as a structural and widespread problem. Two national surveys that study its characteristics identify this population segment as one of the most common targets of violence, with the second-highest rates of homophobic crimes in the world. However, governments have made little effort to study this phenomenon. This document therefore investigates the phenomenon of exclusion in the State of Hidalgo, Mexico, using data from the 2010 National Survey on Discrimination. The methodological approach consists of a descriptive statistical review to examine trends and the construction of analytical profiles of agents of discrimination based on the technique of multiple correspondences with basic demographic variables.